Pengaruh Workshop ASI Eksklusif pada Kader Posyandu Balita terhadap Pengetahuan dan Skill Penyuluhan Kesehatan di Desa Sokaraja Tengah Banyumas - Aprilina, Happy Dwi; Handayani, Diyah Yulistika; Etlidawati, (Jurnal Keperawatan Soedirman, 2017)
Nutrition or the ideal food for babies is breast milk (ASI). Other food or drink cannot replace breast milk. Exclusive breastfeeding in Indonesia is still low. Data Riskesdas reported exclusive breastfeeding in Indonesia only 30.2%. The level of knowledge of mothers on exclusive breastfeeding is still lacking. Implementation of health education on exclusive breastfeeding can be done by many people, one of whom is a toddler Posyandu’s volunteer. This study was to identify effect of exclusive breastfeeding workshop on volunteer Posyandu Balita against knowledge of exclusive breastfeeding in the Central Sokaraja village, Banyumas. The study design using pre-experimental approach to one group pretest-posttest design. The population is all children under five in the village cadres Posyandu Middle Sokaraja 32 cadres Posyandu toddler. The sampling technique total sampling. Statistical test using the Wilcoxon test. The results showed the knowledge gained cadres p 0.000 (